Clinical and Laboratory Characteristics of Patients with Peritoneal Tuberculosis Mimicking Advanced Ovarian Cancer - Maheshwari, Amita; Gupta, Sudeep; Rai, Shweta; Rekhi, Bharat; Kelkar, Rohini; Shylasree, TS; Menon, Santosh; Deodhar, Kedar; Thakur, Meenakshi; Das, Ushasree; Gupta, Stuti; Tandon, Sandeep (South Asian Journal of Cancer, 2021)
Objectives Peritoneal tuberculosis can mimic advanced abdominal malignancy. We describe clinical and laboratory characteristics in a series of female patients with peritoneal tuberculosis who were referred to a tertiary cancer center with a diagnosis of suspected advanced ovarian/primary peritoneal cancer.Materials and Methods Details of clinical features, laboratory results including serum tumor markers, radiological findings, and ascitic fluid evaluation were retrospectively collected from hospital records for patients diagnosed to have peritoneal tuberculosis and reported descriptively.Statistical Analysis Descriptive statistics was performed using SPSS Statistics for Windows software, version 20.0 (SPSS, Chicago, Illinois).Results Between January 2009 and December 2017, 120 patients of peritoneal tuberculosis with a median age 41 years (range, 15–79 years) were identified. Of these 112 (93.3%; 95% CI 88.9–97.8%) patients had ascites and 63 (52.5%; 95% CI 43.6–61.4%) had adnexal mass at presentation. Mean serum cancer antigen 125 (CA-125) level was 666.9 (range, 38–18,554) U/mL. Ascitic fluid was negative for malignant cells in all patients and lymphocyte rich exudate was seen in 103 (91.9%; 86.9–97.0%) patients. Ascitic fluid adenosine deaminase (ADA) level was more than 40 U/L in 107 (95.5%; 95% CI 91.7–99.4%). Ascitic fluid Ziel–Neelsen staining was positive in 4/62 (6.5%; 95% CI 0.3–12.6%) patients while ascitic fluid culture examination for mycobacterium tuberculosis was positive in 7/59 (11.9%; 95% CI 3.6–20.1%) patients. The diagnosis of tuberculosis was based on image-guided biopsy in 44 (36.7%) patients, surgical biopsy in 8 (6.7%) patients, and a combination of clinicoradiological and laboratory features in 68 (56.7%) patients. All patients received standard antitubercular treatment.Conclusions The study results suggest that peritoneal tuberculosis has clinical, radiological, and serological profile which may mimic advanced ovarian/primary peritoneal cancer. Peritoneal tuberculosis should be considered in the differential diagnosis of advanced abdominal malignancy.
Keywords: abdominal tuberculosis; ovarian cancer; primary peritoneal cancer